2017
DOI: 10.1038/ncomms14566
|View full text |Cite
|
Sign up to set email alerts
|

Theory of optimal balance predicts and explains the amplitude and decay time of synaptic inhibition

Abstract: Synaptic inhibition counterbalances excitation, but it is not known what constitutes optimal inhibition. We previously proposed that perfect balance is achieved when the peak of an excitatory postsynaptic potential (EPSP) is exactly at spike threshold, so that the slightest variation in excitation determines whether a spike is generated. Using simulations, we show that the optimal inhibitory postsynaptic conductance (IPSG) increases in amplitude and decay rate as synaptic excitation increases from 1 to 800 Hz.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 63 publications
(122 reference statements)
0
4
0
Order By: Relevance
“…What might be the underlying neurophysiological basis for our observed changes in SO and d I waves with recovery? One possibility is that elevations in extra-synaptic g-aminobutyric acid (GABA) after stroke exp may alter local excitability and thus perturb the ability of global SOs to organize local d. Studies have reported that reducing such tonic inhibition can have a beneficial effect on recovery (Clarkson et al, 2010;He et al, 2019), implying that altered excitation-inhibition (E-I) balance (Kim and Fiorillo, 2017;Xia et al, 2017;Yizhar et al, 2011) plays a role in recovery.…”
Section: Reducing Elevated Tonic Inhibition and Pathological Sleepmentioning
confidence: 99%
“…What might be the underlying neurophysiological basis for our observed changes in SO and d I waves with recovery? One possibility is that elevations in extra-synaptic g-aminobutyric acid (GABA) after stroke exp may alter local excitability and thus perturb the ability of global SOs to organize local d. Studies have reported that reducing such tonic inhibition can have a beneficial effect on recovery (Clarkson et al, 2010;He et al, 2019), implying that altered excitation-inhibition (E-I) balance (Kim and Fiorillo, 2017;Xia et al, 2017;Yizhar et al, 2011) plays a role in recovery.…”
Section: Reducing Elevated Tonic Inhibition and Pathological Sleepmentioning
confidence: 99%
“…Probabilities are typically used to describe the knowledge of scientists, but they can also be used to describe the information in a cognitive or physical model of an observer. This is the basis of Bayesian accounts of biology and psychology that view an organism as a collection of observers that predict and cause the future [21,[30][31][32][33][34][35][36][37][38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…However, we do not think it is overly simplistic for a model of a physical observer to be just a single quantity at a single moment in time. The brain is a multitude of local physical observers, but our initial concern is just a single observer at a single moment [21,22,[33][34][35]. The problem is greatly simplified by the fact that we equate an observer with information, and information with a physical quantity that is local in space and time, and is described by a single number.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that elevated GABAA-mediated tonic inhibition reduces network excitability, and that reducing such inhibition can have a beneficial effect on recovery (Clarkson et al, 2010;He et al, 2019). These studies specifically imply that an altered excitation-inhibition balance (Kim and Fiorillo, 2017;Xia et al, 2017;Yizhar et al, 2011) plays an important role in motor recovery. Thus, we tested the effects of blocking GABAA-mediated tonic inhibition after stroke on the temporal coupling of spindles to slow-waves.…”
Section: Reducing Elevated Tonic Inhibition and Pathological Sleepmentioning
confidence: 99%